2018
DOI: 10.1007/s11356-018-1784-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LncRNA LINC00152 promoted glioblastoma progression through targeting the miR-107 expression

Abstract: Long non-coding RNAs (lncRNAs) LINC00152 plays important roles in the progression of some tumors. However, the role of LINC00152 in human l glioblastoma is still unknown. In this study, we indicated that LINC00152 expression level was upregulated in glioblastoma tissues and cell lines. Overexpression of LINC00152 promoted the U87 and LN229 cell proliferation and invasion. Moreover, overexpression of LINC00152 suppressed the E-cadherin expression, where ectopic expression of LINC00152 promoted the N-cadherin, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…All these reports indicated that there are interactions between miRNAs, lncRNAs and mRNAs in tumours. What's more, it is also elucidated that lncRNAs would influence the progression by sponging miRNAs even in glioma . Herein, we confirmed the interaction between MATN1‐AS1 and miR‐200b/c/429 as well as their negative correlations in glioma tissues.…”
Section: Discussionsupporting
confidence: 68%
“…All these reports indicated that there are interactions between miRNAs, lncRNAs and mRNAs in tumours. What's more, it is also elucidated that lncRNAs would influence the progression by sponging miRNAs even in glioma . Herein, we confirmed the interaction between MATN1‐AS1 and miR‐200b/c/429 as well as their negative correlations in glioma tissues.…”
Section: Discussionsupporting
confidence: 68%
“…It serves as an independent risk factor for disease-free survival (DFS) and overall survival (OS) (Zhang PP et al, 2017). Yu MJ et al, 2017;Cai et al, 2018;Chen X et al, 2018;Liu et al, 2018;Reon et al, 2018;Zhu et al, 2018 Chen et al, 2017;Feng et al, 2017;Li et al, 2017;Ma et al, 2017;Nötzold et al, 2017;Xu et al, 2017;Zhang PP et al, 2017;Reon et al, 2018;Zhang and Li, 2018;Zhao et al, 2018;Liu ZZ et al, 2019 Colon cancer ↑ ↓ Qiu and Yan, 2015;Bian et al, 2017;Nishizawa et al, 2018;Wang X et al, 2018;Yue et al, 2018Zhang et al, 2016 This conclusion has been also confirmed by other reports (Feng et al, 2017;Reon et al, 2018) on the Gene Expression Omnibus (GEO) (Seo et al, 2012) and The Cancer Genome Atlas (TCGA) databases (Collisson et al, 2014). Zhao et al (2018) analyzed the expression profiles of lncRNAs in three pairs of lung adenocarcinoma tissues and adjacent normal tissues.…”
Section: Relation Of Overexpression Of Linc00152 With Worse Prognosismentioning
confidence: 64%
“…12 In addition, another lncRNA, LINC00152, was previously demonstrated to promote glioblastoma progression by targeting miR-107. 28 Similarly, Gius et al 29 showed that KIF23 was overexpressed in normal cervical epithelium obtained from cervical cancer patients. Consistent with our findings, another recent study predicted that KIF23 was a target gene of miR-195.…”
Section: Discussionmentioning
confidence: 96%